Implementation of Public Policy in the Regulation of Street Vendors on Siliwangi Street in Cirebon City - Khalda Nur Fajria; Leni Rohida (Syntax Corporation, 2026)
Street vendor (PKL) management is a public policy issue encompassing community economic empowerment, urban space utilization, and public order. However, the street vendor (PKL) management policy on Siliwangi Street, Cirebon City still faces several obstacles, such as non-compliance by vendors, limited supporting facilities, and differing perceptions between the government and street vendors. These conditions indicate a gap between policy design and the reality of implementation on the ground. This research aims to identify factors influencing the success and obstacles of policy implementation, as well as the local government's steps to optimize street vendor management and empowerment to make it more efficient and sustainable. The study used a descriptive qualitative approach using observation, documentation, and interviews. The results indicate that the Cirebon City Government has implemented the policy through outreach, data collection, shelter provision, and supervision involving the DKUKMPP and the Public Order Agency (Satpol PP). Policy communication has been ongoing, although not yet dialogic. On the other hand, inter-agency involvement and data collection technology support implementation, but limited land, facilities, and budget are obstacles. Furthermore, concerns about declining revenues and the reappearance of street vendors in prohibited areas indicate the need for strengthened participatory communication, improved facilities, and sustainable economic empowerment.